Aktivitas Enzim Selulase dari Khamir Candida sp. dan Debaryomyces sp. yang Diisolasi dari Lahan gambut Taman Nasional Bukit Duabelas Jambi - Kanti, Atit (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTCellulalytic Activity of Candida sp and Debaryomyces sp Isolated from Peat Soil ofBukit Duabelas Natural Park, Jambi. Candida sp. and Debaryomyces sp. YeastDegrading cellulose Isolated from Peat Soil in Bukit Duabelas National Park, Jambi. Theobjective of study was to investigate the characteristic of yeast that are able to solubilizecellulose. The yeast was isolated from soil of Tarnan Nasional Bukit Duabelas Jambi.Out of 2 1 ioslates tested 2 isolates Candida sp. (Isolate J I) and Debaryomyces sp. (IsolateJ2) were able to solubilize Carboxymethyl cellulose. Other isolated soil yeasts wereRhodotor& sp, and C~ptococcusp . Medium acidity during cell cultivation variedbetween 5.8 to 7.2. The CMC-ase activity was 5.9 unit and 5.4 unit for isolate J1 andisolate 52 respectively. The Km of isolate J1 and isolate 52 were 7.7 x 10" and 8.4 x 1 0-2(% b/v) respectively. Vmaks of isolate J1 and J2 was 8.28 xlW3 dan 30.66 x lo-) pgglukosa/ml enzyme /minute, respectively.Key words: Cellulolytic Yeasts, Candida sp., Debaryomyces sp., Enzymes Activity,Taman Nasional Bukit Duabelas